The Effect of Combining Blood Flow Restriction and Plyometric Exercise on Quadriceps Muscle Strength, Functional Ability and Balance Capacity - A Pilot Study Amongst Amateur Soccer Players - Krekoukias, Georgios; Papakonstantinou, Christina; Tsepis, Elias; Fousekis, Konstantinos; Tsekoura, Maria; Aggelopoulos, Pavlos; Billis, Evdokia (International Journal of Innovative Research in Medical Science, 2023)
Football is one of the most popular sports employing a plethora of people around the world. Plyometric exercise and Blood Flow Restriction (BFR) exercise are two different means used to enhance athletic performance in healthy athletes and also during the rehabilitation of musculoskeletal injuries. To our knowledge, the combination of plyometric exercise and BFR has not been studied so far. The aim of this study is to investigate the effect of BFR during plyometric lower limb exercise on quadriceps muscle strength, functional capacity and dynamic balance of the lower limb in amateur football players. This is a comparative study with a parallel 10-week, twice/week intervention in 2 different groups. Group A (N = 5) performed a plyometric exercise program and group B (N = 5) performed the same plyometric exercise program with the simultaneous application of BFR. Outcome measures were 1 Repetition Maximum of the squat exercise, Y Balance Test, Horizontal Countermovement Jump, Vertical Countermovement Jump, and single leg Triple Hop Test (THT). There was statistically significant improvement in both groups in all variable except THT on the non-dominant leg. There was no statistically significant difference between groups. Plyometric exercise, whether applied with or without blood flow restriction, improved strength, balance and functional capacity in male amateur football players